Combining ability and genetic components of yield characteristics, dry matter content, and total carotenoids in provitamin A cassava F1 cross-progeny - Parkes, Elizabeth; Aina, Olufemi; Kingsley, Akuwa; Iluebbey, Peter; Bakare, Moshood (MDPI, 2020)
Cassava is an important root crop in sub-Saharan Africa, largely cultivated for its starchy edible roots. Biofortified cassava varieties with enhanced provitamin A carotenoid content (PVAC) developed through conventional breeding provide a solution for vitamin A deficiency among vulnerable communities. The aim of this study was to use diallel analysis of six provitamin A cassava genotypes to determine the combining ability, genetic components, heritability, and heterosis of the most important yield characteristics and total carotenoids. Genetic variability for measured characteristics were evident. Fresh root yield was mainly determined by non-additive genetic effects, while dry matter content and total carotenoids were determined by additive effects. Total carotenoids were negatively correlated with fresh root yield, indicating that selection for higher provitamin A content could reduce yield. Mid and higher parent heterosis was seen in some of the crosses for fresh root yield, dry matter content, and total carotenoids. Narrow sense heritability was moderate for fresh root yield and dry matter content, and was high for total carotenoids. This study indicated that yield and dry matter content can be improved in provitamin A cassava but that increased provitamin A content may carry a yield penalty.